Enhanced infiltration and morphology of bismuth perovskite in Carbon-stack solar cells – A synergistic effect of electric fields in modified spray technique. (15th July 2022) - Bhavani Korukunda, Tulja; Joshi, Dhavalkumar N.; Meroni, Simone; Watson, Trystan; Dutta, Viresh
Graphical abstract: Improved infiltration of Bi-perovskite in C-PSC stack via modified spray coating using electric field across the nozzle (M-EF) and an additional electric field at the substrate (AM-EF). Highlights: Infiltration of perovskite in C-PSCs is a key factor for the device performance. Spray in conjunction with electric fields (EF) is used to infilter Bismuth perovskite. The EF enhanced crystallinity, opto-electric properties and stability of perovskite. Improved perovskite infiltration is reflected in boosting Jsc of the device. Greener solvent system-based perovskite ink is used for spray deposition. Abstract: Carbon-based perovskite solar cell (C-PSC) is the breakthrough device architecture, with all printable layers, owing to its ease of fabrication and scope of commercialization. However, infiltration of the perovskite into this prefabricated monolithic C-PSC is a cumbersome process since it needs the adequate material to reach the mesoporous TiO2 (m-TiO2 ) layer through a thick C- electrode and ZrO2 (separator) and crystallize uniformly. Herein, using the modified electric field (EF) assisted spray technique and with a greener solvent system for the Bismuth Perovskite (Bi-perovskite), its infiltration in the C-PSC stack is demonstrated. A conventional spray system is modified with two different EFs at the nozzle (M−EF) and the substrate (A-EF). The developed protocol promotes controlled infiltration of perovskite at a faster rate (∼2 mins), addressing the infiltration issue in C-PSCs. Consequently, the efficiency of spray devices is improved by ∼ 80% compared to the drop-casted devices. The enhanced stability of the Bi-perovskite, resulting from the selective plane growth, suggests another significant improvement by employing the proposed spray technique. The substantial efficiency and stability improvement attained using a greener solvent system (Acetone-DMF) add an advantage to the process. Hence, the work highlights the first-ever spray-processed non-lead perovskite using the greener solvent system for a large area hole transport layer (HTL) free C-PSC device.